2022
DOI: 10.1038/s41598-022-23490-5
|View full text |Cite
|
Sign up to set email alerts
|

Learned end-to-end high-resolution lensless fiber imaging towards real-time cancer diagnosis

Abstract: Recent advances in label-free histology promise a new era for real-time diagnosis in neurosurgery. Deep learning using autofluorescence is promising for tumor classification without histochemical staining process. The high image resolution and minimally invasive diagnostics with negligible tissue damage is of great importance. The state of the art is raster scanning endoscopes, but the distal lens optics limits the size. Lensless fiber bundle endoscopy offers both small diameters of a few 100 microns and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…We found that a cascade of U-Net in combination with an EDSR achieves the best image enhancement [9]. Classification is performed using a VGG-19 network.…”
Section: Methods and Results: Cascaded Neural Networkmentioning
confidence: 99%
“…We found that a cascade of U-Net in combination with an EDSR achieves the best image enhancement [9]. Classification is performed using a VGG-19 network.…”
Section: Methods and Results: Cascaded Neural Networkmentioning
confidence: 99%
“…For the reconstruction through the CFB, an additional U-Net is used. 32,33 A more sophisticated network architecture could yield even better results. The reconstruction quality is measured by calculating the peak signal-to-noise ratio (PSNR) between the ground truth and the reconstructed image.…”
Section: Simulation and Training Setupmentioning
confidence: 99%
“…One approach that has gained attention is the utilization of deep learning technology in holographic endoscopy. In this method, the TMs of the fibers are trained by using different conformations, allowing the inference of the TM for arbitrary conformations at a later stage. While promising, this approach has shown effectiveness primarily for simple artificial objects. Another approach involves the placement of a partial reflector at the distal end of a fiber bundle and using the reflection from this reflector as a reference wave to compensate for core-to-core phase retardations …”
Section: Introductionmentioning
confidence: 99%